Pembentukan Digital Trust dalam Live Commerce dan Implikasinya Terhadap Keputusan Pembelian Konsumen - Sashi Azka Ramadhan; Anisa Aprilianti; Shalsabila Rizkiyani; Ade Sobandi; Abi Sopyan Febrianto (Indo Publishing, 2026)
Advances in digital technology have catalyzed the emergence of novel commercial formats, among which live commerce has gained considerable traction as a real-time broadcast selling mechanism that enables direct interaction between vendors and prospective buyers. Although this format enriches the shopping experience with heightened interactivity, establishing and sustaining consumer trust within fully digital transactional contexts commonly termed digital trust remains a fundamental challenge. This study investigates how digital trust is formed through four independent variables: host credibility (X1), live interaction (X2), information quality (X3), and social proof (X4), and examines the extent to which digital trust (Z) mediates these variables' impact on consumer purchase decisions (Y). A quantitative research design employing namely quantitative analysis with multiple regression was adopted. Participants consisted of active users of TikTok Shop and Shopee Live who were at least 17 years old, with a target sample range of 120–150 respondents. Measurement instruments were developed using a five-point Likert scale. The research hypothesizes that all four independent variables positively influence digital trust, which in turn positively affects purchase decisions. The findings are expected to contribute both theoretically and practically to the study of digital consumer behavior, with particular relevance to the live commerce ecosystem in Indonesia.